Islam : - Endress, Gerhard (Edinburgh University Press, 2002)
Hailed as a concise survey of Islamic history and culture, An Introduction to Islam covers everything from Islamic theology and law to the development of the Arabic, Persian, and Turkish languages, from social and economic life in the middle ages to the invention of the Muslim calendar. For the second edition, the text as well as the references and bibliography have been brought up to date.